Knowledge transfer capability among ICT firms in Malaysia - Mhd. Sarif, Suhaimi (2010)
This paper presents the views of managers and knowledge workers of information and communication technology (ICT) firms in Malaysia pertaining to the roles of knowledge stocks, social network, and firm’s environment in creating knowledge transfer capability. Knowledge is important because it enables a firm to be innovative in terms of producing new products and services to the market. Usually innovative firms create knowledge continuously because of the short product/service life cycle. Strategic management and knowledge management literatures suggest a firm with knowledge transfer capability is more innovative. However, based on personal interviews with 12 informants, the study observed that Malaysia’s ICT firms were well equipped with knowledge transfer capability due to over emphasized on profit making over knowledge creation. These firms need to change from where they are now to more knowledge oriented approach if they want to sustain in the ICT industry.